Inducing ovulation with oestradiol cypionate allows flexibility in the timing of insemination and removes the need for gonadotrophin-releasing hormone in timed AI protocols for dairy cows - Ferreira, R. M.; Ayres, H.; Gimenes, L. U. [UNESP]; Torres, F. P.; Lima, F. A.; Veras, M. B.; Guida, T. G. [UNESP]; Sala, R. V.; Baruselli, P. S. (Csiro Publishing, 2017)
The effects of addition of gonadotrophin-releasing hormone (GnRH) to a progesterone plus oestradiol-based protocol and timing of insemination in Holstein cows treated for timed AI (TAI) were evaluated. Cows (n=481) received a progesterone device and 2mg oestradiol benzoate. After 8 days, the device was removed and 25mg dinoprost was administered. Cows were allocated to one of three (Study 1; n=57) or four (Study 2; n=424) groups, accordingly to ovulation inducer alone (Study 1; oestradiol cypionate (EC), GnRH or both) or ovulation inducer (EC alone or combined with GnRH) and timing of insemination (48 or 54h after device removal; Study 2). In Study 1, the diameter of the ovulatory follicle was greater for GnRH than EC. Oestrus and ovulation rates were similar regardless of ovulatory stimuli. However, time to ovulation was delayed when GnRH only was used. In Study 2, cows treated with GnRH or not had similar pregnancy per AI (P/AI) 30 days (41.5% vs 37.3%; P=0.28) and 60 days (35.9% vs 33.0%; P=0.61) after TAI. TAI 48 and 54h after device removal resulted similar P/AI at 30 days (40.3% vs 38.5%; P=0.63) and 60 days (33.8% vs 35.1%; P=0.72). Thus, adding GnRH at TAI does not improve pregnancy rates in dairy cows receiving EC. The flexibility of time to insemination enables TAI of a large number of cows using the same protocol and splitting the time of AI.
Keywords: ovulation stimuli; reproduction efficiency; synchronisation of ovulation